Strategi BMT dalam Mempertahankan Eksistensi Lembaga (Studi Kasus: BMT Nagari Pakan Sinayan) - Meisy Andari; Aidil Alfin (ARZUSIN, 2026)
The existence of Baitul Maal wat Tamwil (BMT) as an Islamic microfinance institution plays an important role in expanding public access to financing and supporting the economic empowerment of the Muslim community. However, several BMT Agam Madani institutions in Agam Regency have experienced declining performance and have even ceased operations, whereas BMT Agam Madani Pakan Sinayan has remained capable of maintaining its existence. Although the sustainability of BMTs has received attention in several studies, research specifically analyzing institutional survival strategies through a SWOT approach at BMT Agam Madani Pakan Sinayan remains limited. This study aimed to analyze the strategies implemented by BMT Agam Madani Pakan Sinayan to maintain its existence and formulate development strategies based on SWOT analysis. The study employed a qualitative approach with a case study design. Informants were selected through purposive sampling, which was subsequently developed using snowball sampling. Data were collected through semistructured interviews, observation, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña combined with SWOT analysis. The results showed that the existence of the BMT was maintained through four main strategies: implementing sound management and governance, strengthening cooperation with the nagari government, increasing customer loyalty through high-quality services, and applying prudential principles in financing. The SWOT analysis identified strengths, weaknesses, opportunities, and threats that served as the basis for formulating the institution’s development strategies. These findings confirm that BMT sustainability is determined by sound governance, service quality, institutional partnerships, and prudent financing management. This study contributes to the development of research on the sustainability of Islamic microfinance institutions and provides practical implications for BMT managers and local governments in strengthening governance, optimizing technology utilization, improving service quality, and expanding institutional collaboration.